First bronchoscopy with cryobiopsy and argon plasma coagulation at Indonesia national referral hospital: Case series - Maulidzy, Achmad Zaki; Marhana, Isnin Anang; Fatmawati, Farah (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2026)
Cryobiopsy has emerged as a superior method for diagnostic endobronchial tissue sampling, offering more extensive and diagnostically valuable specimens than traditional techniques. Argon plasma coagulation (APC), a form of cryoablation, facilitates effective tumour resection and haemostasis with minimal complications. At Dr. Soetomo General Academic Hospital, conventional methods have predominantly been used for lung tumour sampling. These case reports introduced the novel application of cryobiopsy and APC in our institution, showcasing our expertise in advanced bronchoscopic techniques. We report on a 55-year-old male with a T3N1Mx stage IIIA left lung tumour and a 65-year-old male with a T4N2M1b stage IVA right lung cancer. Diagnoses were small-cell lung carcinoma and adenocarcinoma with wild-type EGFR mutation, respectively. Procedures were performed with minimal complications, demonstrating the effectiveness and safety of these techniques. These case reports underscored the potential of cryobiopsy and APC to enhance diagnostic accuracy and therapeutic outcomes, advancing pulmonary oncology care. These techniques provide superior diagnostic accuracy and therapeutic benefits with minimal complications. Our findings support the broader adoption of these advanced bronchoscopic interventions, particularly in settings where traditional methods may fall short.